Poor half billion in South Asia: what is holding back lagging regions? - Ghani, Ejaz (ed.) (New Delhi, 2010)
South Asia is a land of sharp and growing contrasts. It has attracted global attention as an emerging economic powerhouse, but is also home to the largest concentration of people living in conflict, poverty, and malnutrition. With a focus on the poor half billion of South Asia, this volume puts into perspective the colossal task ahead to eradicate poverty and enable inclusive growth in the region. Examining the challenges, successes, and failures of South Asia, it provides fresh perspectives on the links between economic geography, institutions, and globalization. Through a comparative study of spatial disparities in income, poverty, conflict, human development, and gender divides, the essays provide answers to why certain regions are lagging. Combining quantitative data with analytical rigour, they provide innovative short- and long-term policy solutions to overcome the limits to growth and escape poverty traps.
Keywords: Economics causes